2007
DOI: 10.1007/s11002-007-9014-1
|View full text |Cite
|
Sign up to set email alerts
|

Self-referencing and consumer evaluations of larger-sized female models: A weight locus of control perspective

Abstract: Larger-sized models, Self-referencing, Weight locus of control, Brand and advertising attitudes,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 22 publications
2
29
0
5
Order By: Relevance
“…Specifically, we found that labeling a physical activity as fun reduced the amount of calories consumed in side dishes during a meal (study 1), the amount of hedonic food served (study 2), and perception of fun during a race positively influenced the choice of a healthy snack (study 3). In line with previous research (Martin et al 2007), these effects were consistent after controlling for BMI. This is, to our knowledge, the first demonstration of how framing a physical activity may differentially influence actual food consumption.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, we found that labeling a physical activity as fun reduced the amount of calories consumed in side dishes during a meal (study 1), the amount of hedonic food served (study 2), and perception of fun during a race positively influenced the choice of a healthy snack (study 3). In line with previous research (Martin et al 2007), these effects were consistent after controlling for BMI. This is, to our knowledge, the first demonstration of how framing a physical activity may differentially influence actual food consumption.…”
Section: Discussionsupporting
confidence: 92%
“…All of these countries have recently experienced significant Western economic development in recent times. Research (Martin, Veer, & Pervan, 2007;Peck & Loken, 2004;Smeesters & Mandel, 2006) and marketing practice (Dove "Real Beauty" campaign) suggest that the marketers can use more obtainable, realistic, and possibly socially responsible depictions of a feminine body shape that matches their target audience, especially those of older women. What is not certain is how well this research and practice translates into effective and responsible promotions in countries other than the United States.…”
mentioning
confidence: 99%
“…We measured A ad using five 5-point semantic differential items: "like / do not like"; "appeals / does not appeal"; "negative / positive feeling"; " good / bad"; and "irritating / not irritating" (Coulter & Pinto, 1995;Holbrook & Batra, 1987;Mackenzie & Lutz, 1989;Martin, Veer, & Pervan, 2007) (α = .934).…”
Section: Body Mass Index (Bmi)mentioning
confidence: 99%
“…Based on Baker & Churchill (1977), Coulter & Pinto (1995), and Martin et al (2007), we measured purchase intention using four items ("Would you like to JOURNAL OF EUROMARKETING the Internet. However, they occupy senior positions and are highly respected by their peers in most of the emerging economies.…”
Section: Body Mass Index (Bmi)mentioning
confidence: 99%